The science of gun policy: a critical synthesis of research evidence on the effects of gun policies in the United States - Smart, Rosanna (Report, 2024)
In this report, part of RAND's Gun Policy in America initiative, researchers seek objective information about what scientific literature reveals about the likely effects of various gun laws. In the fourth edition of this report, the authors incorporate more-recent research in their synthesis of the available scientific data regarding the effects of 18 state firearm policies on firearm injuries and deaths, violent crime, suicides, the gun industry, defensive gun use, and other outcomes. By highlighting where scientific evidence is accumulating, the authors hope to build consensus around a shared set of facts that have been established through a transparent, nonpartisan, and impartial review process. In so doing, they also illuminate areas in which more and better information could make important contributions to establishing fair and effective gun policies